2005
DOI: 10.1186/cc3886
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction We conducted a prospective observational study from January 1995 to December 2004 to evaluate the impact on recovery of a major advance in renal replacement therapy, namely continuous veno-venous haemodiafiltration (CVVHDF), in patients with refractory septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 31 publications
1
8
0
3
Order By: Relevance
“…The general mortality rate was 2.6%. The mortality rate was much lower than the general mortality rate of MOF patients caused by sepsis or trauma, which was approximately 50%, and nearly 100% when more than 4 organs failed [1] , [2] . In our 156 MOF patients, 118 cases had 2 failing organs, 21 cases had 3 failing organs, 16 cases had 4 failing organs, and 1 case had 5 failing organs; there were 17 cases that required mechanical ventilation, 15 cases had acute heart failure, 13 cases had shock, 10 cases had a coma, and 10 cases had cardiac arrest.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The general mortality rate was 2.6%. The mortality rate was much lower than the general mortality rate of MOF patients caused by sepsis or trauma, which was approximately 50%, and nearly 100% when more than 4 organs failed [1] , [2] . In our 156 MOF patients, 118 cases had 2 failing organs, 21 cases had 3 failing organs, 16 cases had 4 failing organs, and 1 case had 5 failing organs; there were 17 cases that required mechanical ventilation, 15 cases had acute heart failure, 13 cases had shock, 10 cases had a coma, and 10 cases had cardiac arrest.…”
Section: Discussionmentioning
confidence: 74%
“…(b) Neodevelopment of azotemia (serum creatinine increased over 50%) [4] , [7] , [8] , [10] . The MOF was diagnosed when the patient had two or more dysfunctional organs [1] , [2] , [6] .…”
Section: Clinical Data and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is congruent with some data that have shown that failure to correct metabolic acidosis rapidly during CRRT is a strong predictor of mortality. For example, Page et al [ 8 ] have demonstrated that metabolic acidosis was associated with increased lactate levels mainly resulting from circulatory failure. In another study, lactate was shown to be associated with early (48 hours) mortality in patients in need of CRRT by Kawarazaki et al [ 16 ] The authors suggested that lactate, among other variables, could help differentiate acute kidney injury patients who do not benefit from CRRT.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] In patients with septic AKI the lack of improvement of acidosis on CRRT is associated with increased lactate levels, circulatory failure, and high mortality. [ 8 ] Lactate clearance early in the hospital course may indicate a resolution of global tissue hypoxia and is associated with decreased mortality rate in patients with severe sepsis and septic shock, [ 9 ] so lactate clearance has been used as one of the goals of early sepsis resuscitation; [ 10 ] however, it is not clear if these data apply to septic patients in need of CRRT.…”
Section: Introductionmentioning
confidence: 99%